Implementation of ICT on Speaking for Intercultural Communication at Higher Education: Lecturers’ Point of View - Hasyim, Ruslan; Noni, Nurdin; Nur, Sahril (Indonesian TESOL Journal, 2024)
This study investigates the implementation of Information and Communication Technology (ICT) in teaching speaking for intercultural communication from higher education lecturers’ point of view, focusing on pedagogical strategies, challenges, and outcomes. Through a qualitative case study involving three English department lecturers at Universitas Muhammadiyah Sorong, Indonesia. Data were collected via classroom observations, semi-structured interviews, and document analysis. Findings reveal that lecturers leveraged ICT tools such as video conferencing (e.g., Zoom), multimedia simulations, gamified platforms (e.g., Kahoot), and collaborative digital projects to support students’ intercultural competencies, including empathy, adaptability, and critical reflection. Structured activities like impromptu debates, role-plays, and multimedia case studies enabled authentic cross-cultural interactions, aligning with pedagogical frameworks such as the Zone of Proximal Development (ZPD) and Technology Acceptance Model (TAM). Despite ICT’s transformative potential, challenges included resource constraints (e.g., unstable internet, limited hardware), lecturer preparedness, and balancing theoretical knowledge with practical application. Lecturers adapted by integrating personal intercultural experiences, digital storytelling, and asynchronous tools (e.g., Padlet) to foster engagement. The study underscores ICT’s role in bridging cultural divides while highlighting the need for context-sensitive strategies, particularly in multilingual, resource-limited settings. Limitations include a small sample size and reliance on lecturer self-reports, suggesting future research should incorporate student perspectives.